A review on co-pyrolysis of biomass and plastic: insight into synergistic effect and operating condition / Nazriyatul Nazihah Roslan and Hamizura Hassan - Roslan, Nazriyatul Nazihah; Hassan, Hamizura (2020)
Biomass is considered to have a better potential to be used as a renewable energy source to substitute fossil fuels. The production of oil from biomass and plastics can be achieved by pyrolysis process. However, the pyrolysis oil from pyrolysis contains high oxygenated compound which leads to low caloric value and corrosion problems. Many researchers have discussed an alternative technique to enhance the quality and quantity of oil by using copyrolysis process. Co-pyrolysis is a thermal conversion process involving two or more feedstock materials. A comparison between co-pyrolysis of biomass and plastics is established in the present work. This article also focused on several studies based on published articles and books. It was found that production of bio-oil yield depends on biomass feedstock and type of plastics use and compositions such as moisture content, volatile matter, carbon (C), oxygen (O), nitrogen (N), ash and the presence of lignocellulose. This study discussed a comprehensive review on the co-pyrolysis of biomass and plastics influences the bio-oil yield through several point of views, including operating variables such as temperature, heating rate, blending ratio and synergistic effect and characteristics of by products as well. To obtain high grade of bio-oil, the maximum temperature, heating rate and blending ratio are 500℃, 10℃/min, and 1:1 respectively. The hydrogen donation from plastics effect the synergistic effect of biomass and plastics. In conclusion, by utilizing biomass and plastics, the volume of wastes can be controlled in the landfill reduce the consumption of fossil fuels, save the environment and increasing energy security of the nation.